From bite marks to vertical facial phenotype: Investigating the relationship between craniofacial and dental arch parameters using conventional wax and digital models - Dayan, Elis; Kurnaz, Merve; Kuşçu, Özgür Önder; Biren, Sibel; Sepet, Elif (Elsevier, 2026)
Objective: This study aims to investigate whether a relationship exists between craniofacial structures and bite marks, thereby enabling the prediction of facial type based on bite mark characteristics. Materials and methods: Thirty-eight volunteers (aged 19–25) without orthodontic treatment, craniofacial anom alies, or temporomandibular dysfunction participated. Bite marks were created on wax-covered sponge rollers. Intercanine distance, arch depth, and arch length were measured from wax models using a caliper and from intraoral scans using the iTero Scanner. Facial profile photographs were analyzed using GIMP software to calculate FH/GoMe angle and LFH/TFH ratio (Lower face height/Total face height). Statistical analyses included intraclass correlation, Wilcoxon and paired t-tests, and Spearman's correlation (p < 0.05). Results: Significant differences were found between wax and digital measurements except for arch lenght. FH/ GoMe angle correlated with upper and lower wax arch lengths, and LFH/TFH ratio correlated with lower arch length. No correlation was found between the facial type parameters and intercanine and arch depth measurements. Conclusion: Although distortion may influence wax impressions, the correlations observed suggest that certain bite mark metrics—particularly lower arch length—may provide morphologic indicators of facial phenotype. These findings are preliminary and not intended for individual identification; larger, diverse samples are needed to validate their forensic relevance.
Keywords: Forensic odontology; Bite mark; Vertical facial type